Character Value Explored In â€œAyah Mengapa Aku Berbeda?â€ As A Strengthening Strategy in Studentsâ€™ Character Building - Sitohang, Ananda; Siallagan, Kristina; Sitanggang, Sesilia; Sembiring, Yenita (Journal of Teaching of English, 2022)
The purpose of this research is to find out what characters value can be used as a tool to build students' character and how to form the moral message in the film Ayah Mengapa Aku Berbeda. To reveal these objectives thoroughly and in depth, this study used descriptive qualitative data analysis techniques and the researchers showed the film Ayah MengapaAkuBerbeda which is done with data collection techniques by means of interviews, direct observation to schools and to several junior high school students.From the results of the analysis, it is known that the series of events that occurred was the suffering of a deaf girl who lived her life with passion, patience, hard work and her shortcomings were not an obstacle to achieving her goals and being pious person to her parents. The film Ayah Mengapa Aku Berbeda has many characters that can be constructive and can also be applied to students' lives. And from these results, it can be concluded that the research in the film contains several characters namely religious, tolerance, independence, hard work, curiosity, communicative, disciplined, likes to read, honest, creative, appreciates achievement, social care, is responsible for words, and not dependent on others.